How local governments govern culture war conflicts - Chou, Mark 1982-; Busbridge, Rachel (Cambridge elements, 2020)
While local governments have traditionally been thought relatively powerless and unpolitical, this has been rapidly changing. Recent years have seen local governments jump headfirst into a range of so-called culture war conflicts like those concerning LGBTI rights, refugee protection, and climate change. Using the Australia Day and Columbus Day controversies as case studies, this Element rejuvenates research on how local governments respond to culture war conflicts, documenting new fronts in the culture wars as well as the changing face of local government. In doing this, this Element extends foundational research by advancing four new categories of responsiveness that scholars and practitioners can employ to better understand the varied roles local governments play in contentious culture war conflicts